Evaluation of Frictional Contact Stresses in Spur and Helical Gears - SHARANAGOUDA PATIL, SANTOSH (2017)
Stress analysis of gears has become a popular area of research in order to reduce the failures and to optimize the design of gears. Friction between gears causes detrimental effects on gear surface contacts, but there is no effective method to determine the frictional effects on these contacts. Inclusion of friction in the study of gear contact is sparse. Also, friction depends on various other parameters, which are in turn ambiguous to evaluate. Hence, a quantitative study of frictional effects on gear contact problem is therefore essential. Thus, to solve the present problem, a dimensionless factor is needed to be developed which would account for the friction in gear contact stress calculations. A simplified gear contact stress evaluation technique which includes friction needs to be developed. In this work, a 3D frictional Finite Element Method (FEM) was employed for the gear frictional study. A newly developed ANSYS APDL involute profile program for spur and helical gears was used for FE modelling. Frictional coefficient and helix angle were considered as the important geometrical parameters in determining the contact stresses. A few cases of spur and helical gear system were analysed using analytical (AGMA calculations) and experimental test data for validation purposes. The experimentation was carried out using a customised experimental setup, Gear Dynamic Stress Test Rig (GDSTR). The experimental results provided a good correlation with the results of the developed 3D FE models. The validated FE models were analysed and the results showed 15% to 22% rise in gear contact stresses for increased frictional coefficients, which is significant. The FE analysis was further extended and a parametric study was carried out. This work developed a dimensionless friction factor and its function which estimates the significant rise of contact stresses in gears. The mathematically correlated KF function was verified and the inclusion of this factor provides better frictional contact stress evaluation in gears. This provides a simplified frictional measure in gear contact stress calculations.